A Study of Membrane Activity in Rat Prostate Cancer Cells: An Evaluation of the FM1–43 Dye Technique. Issue 1 (February 2000) - Mycielska, Maria E.; Schäfer, Monika; Fraser, Scott P.; Djamgoz, Mustafa B. A.; Bashford, C. Lindsay
Abstract : A study was initiated to test whether the FM1–43 dye technique could beapplied to the study of endocytic membrane activity in two rodent prostatecancer (MAT-LyLu and AT-2) cell lines of markedly different metastaticability. The lipophilic dye FM1–43, which has frequently been used tomonitor endo/exocytic activity in excitable cells was employed. We found, as in excitable tissues, that both strongly metastatic (MAT-LyLu) andweakly metastatic (AT-2) cells in culture take up FM1–43 to give vesicularstaining of a variable pattern, which appeared to differ between the twocell lines. However, unlike excitable tissues, neither cell linesubsequently released the dye. Indeed, both cell lines retained the dyethrough several rounds of cell division suggesting that dye incorporatedby cells does not enter the endo/exocytotic cycle. Uptake of dye wasindependent of temperature, Na + /K+ gradients, pH or metabolism. Wesuggest that passive accumulation of FM1–43 can occur in cancer cells andshould not, automatically, be interpreted as evidence of endocytosis.